Upaya Strategis Pemerintah Kota Surakarta dalam Mewujudkan Profesionalisme Sumber Daya Manusia Aparatur - Henny Juliani (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract The professionalism of human resources of public servants in executing public service tasks, governmental tasks, and specific development tasks are often perceived with bad stigma, particularly in negative issues on quality and performance aspects. Based on this fact, Government of Surakarta Municipality perform strategic efforts in improving the professionalism of human resources of public servants to their quality and performance will increase as well as can realizing prime services to the citizen. This research uses an empirical juridical approach. While the specification of the research is analytical descriptive, and the source of data comprises of primary and secondary data. The result of research was analyzed quantitatively. Based on the research, it can be concluded that in improving the professionalism of human resources of public servants, the Government of Surakarta Municipality perform strategic efforts, namely: 1. They are fulfilling demand of number of human resources of public servants with specific qualification, 2 and improving capacity and quality of human resources of public servants that relevant to improve their competency, 3 and applying e-Performance as a system to evaluate performance of human resources of public servants in manage personal work load as well as organization, performance indicator achievement as a basic calculation of work achievement and incentive reward, 4 and applying discipline penalty in accordance to behavior of human resources of public servants. Strategic efforts of Government of Surakarta Municipality complied with the regulation of PerMenPan dan RB No.38 Year 2018 regarding Measurement of Professionalism of Human Resources of Public Servants, which is measured by using 4 (four) dimension, comprises of a. Qualification, b. Competence, c. Performance, and d. Discipline. Keywords: Public Servants, Government Of Surakarta Municipality Abstrak Penelitian ini bertujuan untuk mengetahui upaya strategis pemerintah Kota Surakarta dalam mewujudkan profesionalisme sumber daya manusia aparatur. Penelitian ini menggunakan metode pendekatan yuridis empiris. Adapun spesifikasi penelitian adalah deskriptif analitis, dengan sumber data yang diperoleh secara primer dan sekunder. Hasil penelitian selanjutnya akan dianalisis secara kualitatif. Berdasarkan hasil penelitian, maka dapat diketahui bahwa dalam meningkatkan profesionalisme SDM Aparatur, Pemerintah Kota Surakarta melakukan upaya strategis yang berupa: 1. Pemenuhan kebutuhan jumlah SDM Aparatur dengan kualifikasi tertentu, 2. Peningkatan kapasitas dan kualitas SDM Aparatur, yang berkaitan dengan peningkatan kompetensi, 3. Penerapan E-Kinerja sebagai sistem penilaian kinerja SDM Aparatur dalam mengelola beban kerja personil maupun organisasi, capaian indikator kinerja sebagai dasar perhitungan prestasi kerja serta pemberian insentif kerja, 4. Penerapan hukuman disiplin yang berkaitan dengan perilaku kerja SDM Aparatur. Upaya strategis yang dilakukan oleh Pemerintah Kota Surakarta tersebut sudah sejalan dengan ketentuan PerMenPan dan RB Nomor 38 Tahun 2018 tentang Pengukuran Indeks Profesionalitas Aparatur Sipil Negara, yang diukur dengan menggunakan 4 (empat) dimensi, meliputi: a. Kualifikasi, b. Kompetensi, c. Kinerja, dan d. Disiplin. Kata kunci: Aparatur Sipil Negara, Pemerintah Kota Surakarta